Climate impacts of the El Niño–Southern Oscillation on South America - Cai, Wenju (2020)
The climate of South America (SA) has long held an intimate connection with El Niño, historically describing anomalously warm sea-surface temperatures off the coastline of Peru. Indeed, throughout SA, precipitation and temperature exhibit a substantial, yet regionally diverse, relationship with the El Niño–Southern Oscillation (ENSO). For example, El Niño is typically accompanied by drought in the Amazon and north-eastern SA, but flooding in the tropical west coast and south-eastern SA, with marked socio-economic effects. In this Review, we synthesize the understanding of ENSO teleconnections to SA. Recent efforts have sought improved understanding of ocean–atmosphere processes that govern the impact, inter-event and decadal variability, and responses to anthropogenic warming. ENSO’s impacts have been found to vary markedly, affected not only by ENSO diversity, but also by modes of variability within and outside of the Pacific. However, while the understanding of ENSO–SA relationships has improved, with implications for prediction and projection, uncertainty remains in regards to the robustness of the impacts, inter-basin climate interactions and interplay with greenhouse warming. A coordinated international effort is, therefore, needed to close the observational, theoretical and modelling gaps currently limiting progress, with specific efforts in extending palaeoclimate proxies further back in time, reducing systematic model errors and improving simulations of ENSO diversity and teleconnections.